On the optimal order of worst case complexity of direct search - Dodangeh, Mahdi (2016)
The worst case complexity of direct-search methods has been recently analyzed when they use positive spanning sets and impose a sufficient decrease condition to accept new iterates. For smooth unconstrained optimization, it is now known that such methods require at most \mathcal {O}(n^2ε ^{-2}) function evaluations to compute a gradient of norm below ε \in (0,1), where n is the dimension of the problem. Such a maximal effort is reduced to \mathcal {O}(n^2ε ^{-1}) if the function is convex. The factor n^2 has been derived using the positive spanning set formed by the coordinate vectors and their negatives at all iterations. In this paper, we prove that such a factor of n^2 is optimal in these worst case complexity bounds, in the sense that no other positive spanning set will yield a better order of n. The proof is based on an observation that reveals the connection between cosine measure in positive spanning and sphere covering.